A holographic description of gravity. (Research'eu results magazine)
To fully understand black hole physics, scientists first need to reconcile Einstein's theory of relativity with quantum physics and, more specifically, make sense of the holographic interpretation of quantum gravity. The QEAH (Quantum Entanglement and Holography) project tool an important step in this direction, by unveiling how standard gravitational quantities should be expressed in terms of their underlying microscopic, holographic description.